1992
DOI: 10.3181/00379727-199-43356
|View full text |Cite
|
Sign up to set email alerts
|

 9-Tetrahydrocannabinol Suppresses Macrophage Extrinsic Antiherpesvirus Activity

Abstract: The effect of delta 9-tetrahydrocannabinol (THC), the major psychoactive component of marijuana, on macrophage intrinsic and extrinsic antiherpesvirus activities was examined. THC had no effect on the capacity of the macrophage-like cells RAW264.7, J774A.1, and P388D1 to take up virus. In addition, replication of virus within macrophages did not occur regardless of drug treatment, indicating that THC had no effect on macrophage intrinsic antiviral activity. In contrast, the cannabinoid exerted a dose-dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…While the immunosuppressive effects of cannabinoids (Cabral and Vasquez, 1992;Morahan et al, 1979) and their modulatory activities on immune cell functions (Cabral and Mishkin, 1989;Fischer-Stenger et al, 1992;Klein et al, 1991) have been reported previously, there is recent evidence supporting the premise that cannabinoids also have anti-inflammatory (Pryce et al, 2003), neuroprotective (Shen and Thayer, 1998), and anti-tumor properties (GalveRoperh et al, 2000). Cannabinoids have been shown to be neuroprotective in a variety of in vitro and in vivo models of neuronal excitotoxicity (van der Stelt and Di Marzo, 2005;McCarty, 2006).…”
Section: Discussionmentioning
confidence: 91%
“…While the immunosuppressive effects of cannabinoids (Cabral and Vasquez, 1992;Morahan et al, 1979) and their modulatory activities on immune cell functions (Cabral and Mishkin, 1989;Fischer-Stenger et al, 1992;Klein et al, 1991) have been reported previously, there is recent evidence supporting the premise that cannabinoids also have anti-inflammatory (Pryce et al, 2003), neuroprotective (Shen and Thayer, 1998), and anti-tumor properties (GalveRoperh et al, 2000). Cannabinoids have been shown to be neuroprotective in a variety of in vitro and in vivo models of neuronal excitotoxicity (van der Stelt and Di Marzo, 2005;McCarty, 2006).…”
Section: Discussionmentioning
confidence: 91%
“…The immunosuppressive effects of cannabinoids, particularly ⌬ 9 -THC, have been reported to impair host resistance to infection (Morahan et al, 1979;Cabral and Vasquez, 1992;Cabral and Dove Pettit, 1998) and to modulate immune cell functions (Cabral and Mishkin, 1989;Klein et al, 1991;Fischer-Stenger et al, 1992). However, mounting evidence supports the notion that certain cannabinoids may have beneficial effects related to their anti-inflammatory (Pryce et al, 2003), neuroprotective (Shen and Thayer, 1998;Marsicano et al, 2003) and anti-tumor properties (Galve-Roperh et al, 2000).…”
Section: Discussionmentioning
confidence: 91%
“…In addition, rat microglia have been reported to synthesize 2-AG in vitro, an event that was proposed as linked to increased proliferation through a CB 2 receptor-dependent mechanism (Carrier et al 2004). In view of these effects on the immune system, it is not surprising that marijuana, THC, and select cannabinoids have been reported to alter resistance to bacterial, protozoan, and viral infections in experimental animals (Morahan et al 1979;Mishkin and Cabral 1985;Marciano-Cabral 1988;Cabral and Vasquez 1992;Klein et al 1994;Cabral and Marciano-Cabral 2004). However, a direct link between susceptibility to infection with the human immunodeficiency virus (HIV) or progression of HIV infection to acquired immune deficiency syndrome (AIDS) has yet to be established.…”
Section: Immune Suppression-effects On Cell-mediated and Humoral Immumentioning
confidence: 94%